Psychosufistic Approach in Islamic Education: Building a Harmonious Learning Environment - Nur Laila Novitasari; Abdul Muhid (Attanwir : Jurnal Keislaman dan Pendidikan, 2025)
A supportive learning environment is a key factor in achieving successful education because it nurtures the intellectual, emotional, and spiritual dimensions of students. This study explores the integration of psychosufistic principles—an approach that combines modern psychology with Sufi spirituality—in shaping a harmonious learning environment. A library research method with a qualitative approach is employed, drawing data from classical and contemporary works on Sufi psychology and Islamic education. Data analysis uses content analysis to identify key themes such as takhalli, tahalli, tajalli, and takziyatun nafs as foundations for character building and spiritual development. The findings indicate that psychosufistic values enrich education by balancing rational intelligence, emotional sensitivity, and spiritual depth. From an Islamic perspective, a conducive learning environment is not limited to technical and physical aspects but is also a manifestation of Islamic values such as compassion, harmony, and moral discipline. The role of educators is crucial in internalising these values, serving not only as knowledge transmitters but also as moral exemplars. The study concludes that integrating psychosufistic principles into Islamic education contributes significantly to the creation of a harmonious environment that enhances motivation, emotional well-being, and character formation. Such integration is essential to address modern educational challenges and foster students who are intellectually capable, emotionally balanced, and spiritually connected.